ADD1 Single Nucleotide Polymorphisms Are Associated With Essential Hypertension Among Han and Mongolian Population in Inner Mongolia Area - Zhang, Yi; Chang, Peiye; Liu, Zhiyue (Frontiers in Genetics, 2022)
Aldosterone synthase (CYP11B2) and α-adducing (ADD1) are candidate genes that play key roles during essential hypertension (EH) incidence. However, the association between their genetic mutations and the risk of EH is unclear. The present study investigated specific single nucleotide polymorphisms (SNPs) from CYP11B2 and ADD1, and their potential role as risk factors for EH based on 423 Mongolian and 410 Han people in Inner Mongolia province. In the allelic model, people with ADD1 rs2239728-A presented a 0.74-fold risk than rs2239728-C, whereas the ADD1 rs4961-T was associated with a 1.37-fold higher risk than allele G in the Han population. The genetic model reported that the rs2239728-A carrier (AA + AC) was 0.59-fold lower than the CC carrier, whereas the rs4961-G carrier (GG + GT) was 0.59-fold lower than the TT carrier in the dominant model. After gender adjustment, people with rs2239728-A was a 0.63-fold risk than –C in EH, but the rs4961-T carrier was associated with a 1.63-times higher risk than –G in females. Haplotype analysis showed that GCCT was associated with essential hypertension in the Han population, and it was a risk factor for EH. Our identification reported novel SNPs of ADD1 with protective significance for EH among females in the Chinese Han population, together with its haplotype GCCT as a risk factor for EH.